Acción colectiva, regresividad fiscal y redistribución regulatoria en la obra de José Luis Villar Palasí - Ruiz Ojeda, Alberto (Revista de Derecho, 2019)
The heart of collective action beats through two cavities, regulation and taxation. Regulation is considered by Villar Palasí as a necessary counterbalance for fiscal regression. This is the effect of excise taxes on which contemporary public finance critically depends to maintain revenue levels inside a budgetary structure unable to produce real income redistribution. The core of the author’s contribution to the Economic Analysis of Public Law is connected to the Neoclassical School and Welfare Economics thought, as explained in this paper. Villar offers a prodigious notion of fair price well grounded on a robust knowledge of the history of ideas and it is applied to define the redistributive role of public bodies through regulation. Villar’s insights are of great help to comprehend the current fiscal equilibrium struggle and collective action institutions functioning.